Caracterização da pesca artesanal na costa do Estado do Ceará, Brasil - Silva, Sônia Maria Martins de Castro e (2004)
The present work has as objectives: (a) to characterize the artisanal fisheries in Ceará State s continental shelf, through a complete description of boat types, gear designs and used fishing methods; (b) to analyze the fish fauna of Camocim, Paracuru, Fortaleza, Caponga and Fortim fishing locations, as concerns composition, space and time distribution, abundance, frequency of occurrence, dominance, diversity, equitability, richness of species and similarity, referring to the rainy and dry seasons; and (c) to address some relative aspects to the ecology of those species. A total of 3,947 boats make up the artisanal fleet (sailboat fleet) of Ceará state, from which 1,831 are small rafts, 1,177 canoes, 410 sailboats, 340 large rafts and 189 sailcrafts. Catching is performed mainly through the use of hand-lines and gillnets. A total of 183,530 captured individuals were classified into 124 species, 50 families and 14 orders, prevailing the order Perciformes, with predominance of the Carangidae, Haemulidae and Sciaenidae families. Out of 124 species, 91 were found to occur in more than one of the studied fishing locations and 97 were observed both in the rainy and dry seasons. The majority of species presented the following characteristics: they inhabit only one of the following fishing areas on the continental shelf: costa (nearshore fishing grounds), risca (intermediate fishing grounds) and alto (distant-water fishing grounds); they live on or close to the sea bottom, especially on rocky substrates; they do not form shoals; they do not migrate; they are more frequently fished for during daytime and yield larger catches in hook-and-line fisheries. Yellowtail snapper (Lutjnaus chrysurus) was considered the most important specie, representing 18.18% of the biomass and 12.32% of the individuals total. Out of 124 species, only 9 were dominant, what contributed to the high diversity indices recorded in all counties but Fortim, because of the high dominance of white grunt (Haemulon plumieri). The Camocim fishing location presented the largest species richness and an outstanding participation in the biomass (59.95%) and the individuals total (50.89%). The smallest similarity index values were observed when Camocim and Paracuru fishing locations were compared to Fortaleza, Caponga and Fortim. Furthermore, a greater evenness was observed between fishing locations of the western coast (Camocim and Paracuru) and those of the eastern coast (Caponga and Fortim), including Fortaleza, which is the cornerstone of Ceará state s coastline. Given the relevance of the artisanal fisheries and the richness of the fish fauna that make up their commercial catches, it is highly desirable for ecological studies to be pursued in relation to such resources, to the effect that knowledge is obtained and directed to a better understanding of that ecosystem and to a sound management of its exploitation.